STRATEGI KOMUNIKASI PEMERINTAHAN DALAM MENINGKATKAN PARTISIPASI MASYARAKAT PADA PEMBANGUNAN DESA WISATA TUKTUK SIADONG KABUPATEN SAMOSIR - Besti Rohana Simbolon; Fenni Khairifa (Jurnal Darma Agung, 2018)
The development of tourism in the Lake Toba area was more of a material for seminars and studies of urban communities. Almost of ​​the people in Lake Toba area did not know what their village tourism event was. Therefore, this study sought to find out how the government communication of Samosir Regency to the community, especially in the Tuktuk Siadong Village. This research used desciptive qualitative approach. The subject was Secretary of Samosir Service, Head of Tuktuk Siadong Village and community and Chair of Pokdarwis in Tuktuk Siadong village. The sampling technique was based on purposive sampling for elements of the village community. Collecting data is done by observation, interviews and documents. The results’s that the Government is less consistent in inviting people to be involved in events carried out according to the annual tourism event calendar. The Chairperson of Pokdarwis said that they did not participate in tourism activities in 2017 and 2018. The community was not the same in receiving information from the government. But the government has used almost all media, namely social media Facebook, newspapers such as SIB Daily, Kompas, Medan Tribun, Medan Bisnis and a flight magazine. Television such as Metro TV, Net TV, Evarina TV and Kompas TV are more widely used for national events. But everything is more informative. The obstacles to lack of participation are the lack of credibility of government communicators, the lack of a communication target. The government's focus is still more on people outside Samosir. It is affected by the lack of communication by the community leaders.